Development and validation of stability indicating RP-HPLC method for Simultaneous determination of Hydrochlorothiazide and Nebivolol Hydrochloride in pharmaceutical dosage form - Ravi Challa; N.V.S. Naidu; K. Rambabu (International Journal of Pharmacy and Analytical Research, 2016)
A stability-indicating RP-HPLC method has been established for determination of Hydrochlorothiazide (HCTZ) and Nebivolol hydrochloride (NBL) in combine dosage form under different stress conditions. The drug substances were subjected to stress by hydrolysis (0.1N HCl and 0.5NaOH), photochemical, and UV degradation (254 nm). Both the drugs were degraded under selected experimental conditions. Successful separation of the drugs from the degradation products was achieved on a Hypersil BDS C18, 150x4.6, 5µ column with 50:50 (v/v) Mixed buffer and Methanol in the ratio 50: 50. 2.6 gms of potassium hydrogen phosphate and 0.6gms of dipotasssium hydrogen phosphate were dissolved in 1000 ml distilled water, pH was adjusted 5.5±0.1 with dilute orthophosphoric acid as mobile phase. The method was linear over the concentration range of 6.250-38.750 μg mL-1 (r2 > 0.991), with limits of detection and quantitation (LOD and LOQ) of 0.3061 and 0.9276 μg mL-1, respectively, for HCTZ and 2.500-15.000 μg mL-1 (r2 > 0.991) with LOD and LOQ of 0.489 and 1.4815 μg mL-1, respectively, for NBL. The method was validated for specificity, selectivity, accuracy, and precision. This method was reproducible and selective. As the developed method could effectively separate the drugs from their degradation products, it can be used as stability -indicating.